Simultaneously improving thermopower and electrical conductivity via polar organic solvents aided layer-by-layer technique. (15th March 2020) - Sun, Xiaomeng; Sun, Tingting; Lu, Xiaofang; Wang, Lianjun; Jiang, Wan
Abstract: In recent years, organic/inorganic hybrids capture wide attention due to their advantages in endowing composites with both high Seebeck coefficient and low thermal conductivity originating from inorganics and polymer, respectively. However, simply blending tend to weaken this advantage, resulting in lower thermoelectric performance than that of single organics or inorganics. Here we propose a polar organic solvents aided layer-by-layer (OS-LbL) technique to prepare high performance nanocomposite films comprising poly(3, 4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) and Sb2 Te3 nanocomposites. Polar organic solvents not only promote the dispersion of Sb2 Te3 nanoplates but also post-treat the PEDOT:PSS layer at the hetero-junction interface, successfully increasing the electrical conductivity and thermopower at the same time. Besides, the organic/inorganic interface inducing by OS-LbL promotes a low thermal conductivity of 0.0522 Wm −1 K −1 . As a result, a maximum ZT value up to 0.10 at room temperature. The results show that using OS-LbL method to combine PEDOT:PSS with Sb2 Te3 nanoplates is a promising pathway to achieve polymer-based, high-performance thermoelectric applications.